2022
DOI: 10.1038/s41586-022-05432-3
|View full text |Cite
|
Sign up to set email alerts
|

T cells specific for α-myosin drive immunotherapy-related myocarditis

Abstract: Immune-related adverse events, particularly severe toxicities such as myocarditis, are major challenges to immune checkpoint inhibitor (ICI) utility in anti-cancer therapy1. The pathogenesis of ICI-myocarditis is poorly understood. Pdcd1-/-Ctla4+/-mice recapitulate clinicopathologic features of ICI-myocarditis, including myocardial T cell in ltration2. Single cell RNA/T cell receptor (TCR) sequencing on the cardiac immune in ltrate of Pdcd1-/-Ctla4+/-mice identi ed activated, clonal CD8+ T cells as the dominan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
157
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(184 citation statements)
references
References 64 publications
8
157
0
1
Order By: Relevance
“…Since the first description of cases with fulminant immune checkpoint inhibitor (ICI) myocarditis in 2016, there has been a vivid interest in identifying the culprit process, if not the nature and molecular target of T cells felt to have gone rogue. In a genetic mouse model with homozygous knockout of Pdcd1 and heterozygous deletion of Ctla4 , Axelrod et al 6 identified highly activated and clonally expanded CD8 T cells as the dominant immune population and depletion of CD8 T cells but not CD4 T cells nearly completely prevented the 50 mortality rate otherwise seen. In a candidate auto-antigen approach, alpha-myosin was identified as one leading target, noted also in three patients with ICI myocarditis.…”
mentioning
confidence: 99%
“…Since the first description of cases with fulminant immune checkpoint inhibitor (ICI) myocarditis in 2016, there has been a vivid interest in identifying the culprit process, if not the nature and molecular target of T cells felt to have gone rogue. In a genetic mouse model with homozygous knockout of Pdcd1 and heterozygous deletion of Ctla4 , Axelrod et al 6 identified highly activated and clonally expanded CD8 T cells as the dominant immune population and depletion of CD8 T cells but not CD4 T cells nearly completely prevented the 50 mortality rate otherwise seen. In a candidate auto-antigen approach, alpha-myosin was identified as one leading target, noted also in three patients with ICI myocarditis.…”
mentioning
confidence: 99%
“…Ongoing studies are interrogating these TCR sequences of clonally expanded CD8 + autoimmune mediators to determine antigen targets in thyroid IRAE. Clonal expansion of T cells has been linked to IRAE risk in two recent studies (22, 45) , including clonal expansion of CD8 + T cells in a mouse model of ICI-associated myocarditis (45) . Importantly, whether clonal expansion also occurs in human ICI-associated myocarditis is unknown as this study did not evaluate immune infiltrates in the tissues of ICI-myocarditis patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a recently published manuscript, scRNA-seq or TCR sequencing performed on Pdcd1 −/− Ctla4 +/− mice showed expansion of activated, clonal CD8 + T cells, with alpha-myosin found as an autoantigen. 11 These findings suggest promising therapeutic targets to treat cardiac IRAEs.…”
Section: Single-cell Immune Profiling Of Cardiac Iraesmentioning
confidence: 91%